2012
DOI: 10.1016/j.juro.2011.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Detection of Renal Cell Carcinoma is an Independent Prognostic Marker: Results of a Long-Term, Whole Population Study

Abstract: With increased incidence and unchanged mortality the survival of patients with renal cell carcinoma has improved. This is mainly related to a steep increase in incidental detection. Incidental detection affects survival favorably and to a greater extent than can be explained by lower stage compared to the survival of patients diagnosed with symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 27 publications
2
32
0
2
Order By: Relevance
“…Asymptomatic renal tumours were reported to have a favourable independent effect on prognosis in two large case series from Italy and Iceland (Ficarra et al, 2003;Palsdottir et al, 2012). This trend is similarly found in our RCC patients where symptomatic tumours predict shorter survival.…”
Section: Discussionsupporting
confidence: 84%
“…Asymptomatic renal tumours were reported to have a favourable independent effect on prognosis in two large case series from Italy and Iceland (Ficarra et al, 2003;Palsdottir et al, 2012). This trend is similarly found in our RCC patients where symptomatic tumours predict shorter survival.…”
Section: Discussionsupporting
confidence: 84%
“…CCRCC is by far the most common renal cancer histological variant, accounting for 75 to 80% of renal neoplasms in adults 7 . CCRCC is a clinically aggressive neoplasm, where radical surgery is the only treatment with significant impact on patient survival 8 . Chemo- and radiotherapy are inefficient so far and modern targeted therapies obtain only partial results 9 .…”
Section: The Contextmentioning
confidence: 99%
“…Vimentin is considered as a potential molecular target for cancer therapy but its specific role remains unclear as well [4,27]. Moreover, vimentin is used as a reliable biomarker in differentiating certain types of renal cell carcinomas [32]. It has been shown that vimentin is expressed in the majority of clear cell and papillary renal cell carcinomas; however, it is rarely expressed in oncocytoma and chromophobe renal cell carcinomas [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, vimentin is used as a reliable biomarker in differentiating certain types of renal cell carcinomas [32]. It has been shown that vimentin is expressed in the majority of clear cell and papillary renal cell carcinomas; however, it is rarely expressed in oncocytoma and chromophobe renal cell carcinomas [32,33]. Therefore, vimentin may assist in confirming diagnoses and having a prognostic value regarding each subtype of RCC.…”
Section: Introductionmentioning
confidence: 99%